Polyphenols and Pharmacological Screening of a Monarda fistulosa L. dry Extract Based on a Hydrodistilled Residue By-Product - Shanaida, Mariia; Hudz, Nataliia; Jasicka-Misiak, Izabela; Wieczorek, Piotr P. (Frontiers in Pharmacology, 2021)
This study aimed to determine the composition and content of polyphenols in the dry extract obtained from the hydrodistilled residue by-product of the wild bergamot (Monarda fistulosa L., Lamiaceae Martinov) herb (MFDE), and to evaluate its safety and pharmacological properties. The total phenolic content (TPC) in the MFDE was 120.64 mg GAE/g. The high-performance liquid chromatography (HPLC) analysis showed the presence of a plethora of phenolic compounds including hydroxycinnamic acids and flavone derivatives in the MFDE, with rosmarinic acid and luteolin-7-O-glucoside being the main components. With an IC50 value of 0.285 mg/mL, it was found to be a strong DPPH radical scavenger. The acute toxicity study results indicate that the oral administration of MFDE to rats at doses 500–5000 mg/kg did not produce any side effects or death in animals which indicates its safety. The results of the in vivo assay showed that the MFDE dose-dependently inhibited paw oedema, and significantly reduced the number of writings in mice induced by the acetic acid injection suggesting its potent anti-inflammatory and analgesic activity, respectively. The conducted studies revealed that M. fistulosa hydrodistilled residue by-product could be regarded as a new natural source of polyphenols with valuable pharmacological properties.